Effective-Practical and Creative (Heuristic) Pedagogical Technologies of Students' Self-Development - Aigul Khafizova; Venera Zakirova (ARPHA Proceedings, 2019)
Creative self-development through educational technology is relevant in modern education. The article shows the basic components of educational technology that can be applied in teaching. The usage of pedagogical technologies by teachers allows them to engage students and create a favorable climate during study. At the same time, students are developing their creative thinking, personal, intellectual and creative abilities.